The relationship between the age of onset of hypertension and chronic kidney disease: a cross-sectional study of the American population - Qiu, Lanlan; Wu, Bo (Frontiers in Cardiovascular Medicine, 2024)
BackgroundHypertension can damage multiple target organs. The younger the age of onset of hypertension is, the greater the risk of cardiovascular disease (CVD) and cardiovascular death. Chronic kidney disease (CKD) is a complication of hypertension, but few studies have investigated the relationship between the age of onset of hypertension and CKD.ObjectiveWe investigated the relationship between the age of onset of hypertension and CKD.MethodWe analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2007–2018. A total of 30,613 participants were assigned to one of four groups. Group 1, no hypertension (n = 19,516); Group 2, age of onset <35 years (n = 2,180); Group 3, 35≤ age of onset <45 years (n = 2,128); and Group 4, age of onset ≥45 years (n = 6,789). Logistic regression analysis was used to evaluate the relationship between the age of onset of hypertension and CKD.ResultsAfter adjusting for potential confounders, a younger age at onset of hypertension was associated with a greater risk of developing CKD compared with the absence of hypertension (Group 2 OR: 2.52, 95% CI: 1.53–4.14, P < 0.001; Group 3 OR: 1.59, 95% CI: 1.01–2.51, P = 0.048; Group 4 OR: 1.54, 95% CI: 1.00–2.38, P = 0.050).ConclusionsThere was a strong association between the age of onset of hypertension and CKD. The younger the age of onset of hypertension is, the greater the risk of CKD.